Evaluation of food choices: women basketball players on different days - Uy, N.; Köse, B. (International Journal of Sport Nutrition and Exercise Metabolism, 2025)
This study involved 33 professional female basketball players from the Women`s Basketball Super League of the Turkish Basketball Federation during the 2023-2024 season who volunteered to participate. The objective was to evaluate the food choices of these athletes on different days. General characteristics of the players, training information, dietary habits, an Athlete Food Choice Questionnaire (AFCQ) and the Digital Food Visuals Catalog (DFVC) were surveyed both face-to-face and online. The DFVC was applied at three different times to test food choices after training, after matches, and on free days. Anthropometric measurements of the participants were also taken by researcher. Of the basketball players, 64% stated that they had received nutrition education. While 73% of the players mentioned that there were foods they avoided during the season, 27% said there were no foods they avoided. Among those who reported avoiding certain foods, 24% mentioned fast food, 42% mentioned alcohol, 22% mentioned sweets and 12% mentioned packaged snacks. Regarding times of unrestricted eating, 67% of the players cited their free day, 30% mentioned after winning a match, and 3% mentioned after losing a match. According to the DFVC, the highest-scoring food group on training days was the meat, chicken, fish, and legumes group. On match days and free days, the highest-scoring food group was fast food. Despite most players indicating that they avoid fast food, the high scores for fast food choices after matches and on free days suggest that food choices vary on different days. In the AFCQ, the sub-factor with the highest average score was ``sensory appeal`` and ``performance`. The sub-factor with the lowest score was "nutritional characteristics of the food". Although the competitive season had not ended, it is possible that the players made food choices based on sensory appeal rather than performance and nutritional content factors after matches and on free days. In conclusion, it was found that the food choices and factors influencing these choices of female basketball players varied on training, match, and free days. Accordingly, it is recommended that nutrition programs specific to different days be organized according to the individual needs of the players and that food choices be optimized.